14 Women empowering women. (3rd November 2019) - Clare, Sarb; Faloon, Sarah; Yan, May
Abstract : 76% of NHS workers are female yet only 36% are in senior positions. Female doctors dominate medical school with the majority at 56%, however only 36% are Medical Consultants, 11% are surgeons and only 25% are Medical Directors. Women bring unique qualities within leadership such as compassion, innovation, sincerity and empathy, which are key for balance to any team. To address this issue a Deputy Medical Director, RCP tutor and CMT delivered a one day national free conference aimed at medical female doctors entitled 'Women Empowering Women' to enable, educate, inspire and empower women to apply for senior positions within the NHS. The day took place at the Sandwell and West Birmingham NHS Trust. Delegates from across the UK attended. Women bring unique qualities within leadership such as compassion, innovation, sincerity and empathy, which are key for balance to any team. The day involved inspiring talks from females in leadership and management roles, including the President of the Women's Federation as well as workshops including Research and Academia, Management and Leadership as well as Teaching and Education. Further workshops included having babies and less that full time working as well as self care. The key aspects that were being addressed was Role modeling – showcasing individuals who are in senior leadership positions and sharing their journey ' If uou can see it you can be it'. Processes – maternity rights to application of jobs were addressed. Mindset– positivity and surrounding yourself with energy and removing the imposter syndrome mentality. A workshop addressing self - defence and dealing with inappropriate behavior in the workplace was also very popular and stories were heard as well as strategies moving forward to address this. From this day many initiatives are being generated at our Trust including a Women's network and mentoring scheme for females.